PERSEPSI MASYARAKAT DESA BUNGBARUH KECAMATAN KADUR KABUPATEN PAMEKASAN TERHADAP PENGGUNAAN MCK - Subaidillah Fansuri; Dwi Deshariyanto; Anita Intan Nura Diana (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2023)
Welfare and environmental quality which is still low in Indonesia is a problem that is almost the same in all settlements, benchmarks for the level of welfare and the low quality of the community's environment can be seen from the houses that people live in. The basic thing that can be identified from a bad environment can be seen from the factors that most influence the quality of the housing itself such as drainage, clean water distribution network, garbage disposal, toilet facilities, density of settlements and poverty. This study intends to examine perceptions about the behavior of the people of Bungbaruh Village regarding environmental health and individual and cubicle sanitation related to the absence of MCK facilities in the village. With a sample size of 55 families, namely the people of Dusun Durbugan II, Bungbaruh Village, Kadur District, Pamekasan Regency. Unhealthy behavior is influenced by educational factors, low income, knowledge, hereditary habits, the absence of toilet facilities so that some people still use open spaces as a means for defecating (BAB). The creation of a clean and healthy environment will be obtained by the behavior of the community to change behavior. Efforts that can be made are increasing public awareness through counseling from related parties and providing adequate toilet facilities